Analysis of physiological and metabolite response of Celosia argentea to copper stress. (18th January 2021) - Wang, S.; He, T.; Xu, F.; Li, X.; Yuan, L.; Wang, Q.; Liu, H.
Abstract: Copper‐tolerant (Cu) plants with high ornamental value play an important role in the ecological restoration of the copper tail mining area. We first discovered Celosia argentea adaptability in a copper mine area in China; however, its resistance to Cu and the underlying mechanism are not clear. In this study, C. argentea was selected for pot culture experiments. Its heavy metal accumulation and translocation, physiological and metabolic products were analysed under different growth concentrations of Cu (0–2400 mg.kg −1 ) stress. Our results indicated that roots strongly accumulated Cu 2+ . Oxidative stress defence mechanisms were activated in leaves under Cu treatment. Higher Cu concentrations triggered higher electrolyte leakage (EL), Malondialdehyde (MDA), superoxide dismutase (SOD) and peroxidase (POD) activity, and consequently a higher capacity to scavenge oxygen radicals and maintain cellular membrane integrity. In the citrate cycle, some amino acids and sugars related to biological pathways were altered in C. argentea exposed to Cu stress. Metabolomics data revealed that C. argentea used elevated sugar content as an antioxidant to regulate reactive oxygen species (ROS). Some organic acids and amino acids were up‐regulated compared with the control, indicating that these may chelate Cu in cells to remove excess Cu 2+ . The up‐regulation of polyamines and some organic acids may mitigate oxidative stress. These results indicate that C. argentea could be used as a Cu‐tolerant plant in Cu mine restoration. Its Cu tolerance mechanism also provides a basis for future plant improvement or breeding for use in mine restoration. Abstract : Celosia argentea adapts to copper stress by accumulating Cu 2+ in roots, activating the defense mechanism of oxidative stress, and regulating the contents of carbohydrates, acids and amines in vivo .